The Aesthetics of Transgression in Siri Hustvedt's THE SUMMER WITHOUT MEN. Issue 2 (3rd April 2019) - Rajendran, Punnya
Abstract: The Summer Without Men (2011) brings together several strands of thought that have characterized Siri Hustvedt's oeuvre, exemplifying most notably the manner in which Husvedt's fictional strategies are informed by her favorite conceptual triad of aesthetics, gender and psychiatry. The structure of transgressions in TSM is crucial to the text's peculiar enunciation of gender, and this paper seeks to explore the potential criticality to the term 'transgression' because it allows us to consider something like a 'partial subject' that escapes gender itself. Driven mostly by the centrality of mental illness and convalescence to the plot, my own animation of the term here is derived largely from Deleuze & Guattari's concept of 'partial subjectivation', from which I also borrow the possibility of thinking esthetically, rather than politically or representationally, about gender. This paper identifies to that effect, a series of Deleuzian 'becomings' in the novel which constitute its esthetics of transgression, forming its own peculiar treatment of gender as a creative flux rather than a juridical concept.